Ecdysone: Structures and Functions - Smagghe, Guy (Springer Netherlands : Imprint: Springer, 2009)
Ecdysone is the steroidal prohormone of the major insect moulting hormone 20-hydroxyecdysone. It groups with its homologues the steroidal molting hormones in arthropods, but they also occur in other phyla where they can play different roles. Besides ecdysteroids appear in many plants mostly as protection agents (toxins or antifeedants) against herbivorous insects. The important developments and achievements in modern ecdysone science since the first edition in 1989 by J. Koolman have led to this new revised, expanded and retitled reference work. New chapters in this edition include RNA interference, the ecdysone receptor crystal structures and structure activity relationships, etc. Each article may also be read independently, as a review of that particular subject. Complete up-to-date coverage of many important topics - the book is divisible into five conceptual areas: (1) Distribution and diversity of ecdysteroids in the two kingdoms is still basis, (2) In the post-genomic era, ecdysteroid genetic hierarchies in insect growth and reproduction, (3) Role of cross talk of genes and growth factors in ecdysteroid titers and signaling, (4) Ecdysteroids function through nuclear and membrane receptors, and (5) Ecdysteroids in modern agriculture, medicine, doping and ecotoxicology. Each of the 23 chapters is written by scientists active in the reviewed research area and a truly distinguished international team of contributors has been chosen. Ecdysone, Structures and Functions will be of immense use and contains essential information for scientists, students, and professionals alike in entomology, endocrinology, physiology, chemistry, and agricultural, plant, biomedicine and environmental sciences.